Oxazole Synthesis from Isocyanides - El Kaïm, Laurent; Grimaud, Laurence; Patil, Pravin (Synlett, 2012)
A new synthetic path toward oxazoles starting from isocyanides is presented. This two-step oxazole preparation involves a bromination–cyclization followed by a Suzuki cross-coupling.
Keywords: oxazoles; Suzuki; palladium; isocyanides; dihalogenoisocyanides